2005
DOI: 10.1007/s00216-005-3173-9
|View full text |Cite
|
Sign up to set email alerts
|

Uranium analysis in urine by inductively coupled plasma dynamic reaction cell mass spectrometry

Abstract: Urine uranium concentrations are the best biological indicator for identifying exposure to depleted uranium (DU). Internal exposure to DU causes an increased amount of urine uranium and a decreased ratio of 235U/238U in urine samples, resulting in measurements that vary between 0.00725 and 0.002 (i.e., natural and depleted uranium's 235U/238U ratios, respectively). A method based on inductively coupled plasma dynamic reaction cell mass spectrometry (ICP-DRC-MS) was utilized to identify DU in urine by measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…All participants signed a written informed consent document. [Ejnik et al, 2005;Gray et al, 2012]. Urine U concentrations were standardized on the basis of urine creatinine concentrations to account for urine dilution to obtain mg U/g creatinine [Karpas et al, 1998;McDiarmid et al, 2000].…”
Section: Methodsmentioning
confidence: 99%
“…All participants signed a written informed consent document. [Ejnik et al, 2005;Gray et al, 2012]. Urine U concentrations were standardized on the basis of urine creatinine concentrations to account for urine dilution to obtain mg U/g creatinine [Karpas et al, 1998;McDiarmid et al, 2000].…”
Section: Methodsmentioning
confidence: 99%
“…The detection limit for quantifying total U in urine using the ICP-DRC-MS technique is 0.1 ng l K1 , an improvement in sensitivity of 200-fold compared to KPA analysis. Accurate isotopic analysis for calculating the U 235 /U 238 ratio in urine specimens is also possible using this quadrapole ICP-DRC-MS technique for samples with U concentrations as low as 10 ng l K1 (Ejnik et al 2005). With this capability, it is possible to calculate the amount of DU in a urine sample that also contains natural U at total U concentrations of 10 ng l K1 and above, thus providing direct evidence of DU exposure.…”
Section: Methods For Measuring Uranium Body Burden and Systemic Exposmentioning
confidence: 99%
“…Other techniques developed for solving this problem involve magnetic sector high-resolution ICP-MS instruments or more extensive sample preparation to first remove the uranium from matrix constituents (Gwiazda et al 2004). A QA/QC comparative study involving multiple laboratories using either the ICP-DRC-MS or high-resolution magnetic sector instruments (Gwiazda et al 2004;Ejnik et al 2005) showed excellent correlations between these techniques for total U uranium and U 235 /U 238 ratio results at urine U concentrations as low as 10 ng l K1 .…”
Section: Methods For Measuring Uranium Body Burden and Systemic Exposmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Oxygenation is an effective way of avoiding spectral interferences by producing an oxide ion free from interfering molecular ions or by oxygenating the isobaric interfering ions. [33][34][35][36][37][38][39][40][41][42][43] However, the effectiveness of O2 has not been evaluated sufficiently and the underlying mechanism of oxygenation in the reaction cell has not been fully elucidated, although the mechanisms underlying the use of NH3 and CH4 have been discussed by several researchers. We investigated the mechanism of oxygenation by using the bond energy and the enthalpy change (ΔH) between the ions and O, and demonstrated the usefulness of theoretical calculations for elucidating reaction mechanisms in DRCs.…”
Section: Introductionmentioning
confidence: 99%